2017
DOI: 10.1371/journal.pgen.1006992
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial heparan sulfate regulates Sonic Hedgehog signaling in lung development

Abstract: The tree-like structure of the mammalian lung is generated from branching morphogenesis, a reiterative process that is precisely regulated by numerous factors. How the cell surface and extra cellular matrix (ECM) molecules regulate this process is still poorly understood. Herein, we show that epithelial deletion of Heparan Sulfate (HS) synthetase Ext1 resulted in expanded branching tips and reduced branching number, associated with several mesenchymal developmental defects. We further demonstrate an expanded F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 72 publications
0
29
1
Order By: Relevance
“…In our recent study, we examined the role of epithelial HS in lung branching morphogenesis and demonstrated a surprisingly expanded distribution of Fgf10 expression and increased Fgf signaling activity in lung buds (He et al, 2017). The data shown here are very different from what we observed in the lung buds, raising an interesting question of the specific activities of HS in regulation of the Fgf signaling pathway.…”
Section: Epithelium Hs Regulates Embryonic Stomach Developmentcontrasting
confidence: 76%
See 2 more Smart Citations
“…In our recent study, we examined the role of epithelial HS in lung branching morphogenesis and demonstrated a surprisingly expanded distribution of Fgf10 expression and increased Fgf signaling activity in lung buds (He et al, 2017). The data shown here are very different from what we observed in the lung buds, raising an interesting question of the specific activities of HS in regulation of the Fgf signaling pathway.…”
Section: Epithelium Hs Regulates Embryonic Stomach Developmentcontrasting
confidence: 76%
“…Mice deficient in one allele of Ext1 appeared to be normal in terms of the gastrointestinal morphology, therefore Ext1 fl/+ ; Shh-Cre mice were used as controls. In contrast, Ext1 mutant mice died shortly after birth due to respiratory defects (He et al, 2017), and exhibited several gastrointestinal anomalies, e.g. small stomach and abnormal intestines ( Fig.…”
Section: Depletion Of Epithelial Hs Leads To Gastric Hypoplasiamentioning
confidence: 99%
See 1 more Smart Citation
“…80 Genetically abolish heparan sulfate in the lung epithelial cells leads to reduced SHH production in the epithelial and expanded Fgf10 expression in the underlying mesenchyme in the lung development. 83 Shh secreted by the palatal epithelium signals to the underlying palatal mesenchyme and regulate Fgfs expression. 1 Fgfs, in return, can either positively or negatively regulate SHH expression in the epithelium.…”
Section: Hspgsmentioning
confidence: 99%
“…HSPG-modulated shedding also represents a useful model to explain functional links between cell-surface HS biosynthesis and Hh bioactivation in lung [ 106 ], spinal cord [ 60 ] and fly wing [ 59 ] development in vivo. Moreover, Scube2-regulated shedding provides an explanation for the compensated loss of embryonic Hh function as a consequence of simultaneous knockdown of all three Scube genes in triple MO embryos [ 68 ] by increased ligand expression.…”
Section: Proposed Model Of Indirect Scube2 Effects As Enhancers Ofmentioning
confidence: 99%